2017
DOI: 10.1093/ejcts/ezx292
|View full text |Cite
|
Sign up to set email alerts
|

How does descending aorta geometry change when it dissects?

Abstract: Type B aortic dissection increases the diameter, length and volume of the descending thoracic aorta. The predissection aortic diameter most closely resembles the post-dissection maximum diameter of the true lumen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 16 publications
(21 reference statements)
2
45
0
Order By: Relevance
“…Okuno et al15 reported an increase in the descending aorta from 10.9±2.9 to 12.9±3.8 mm after induced dissection in an experimental study using the swine model. Rylski et al11 reported a geometrical change in the descending aorta in 25 patients with acute type B aortic dissection compared with enhanced CT scans within 2 years before dissection, which is similar to the present study. They found that the mean total diameter changed from 28.2 to 34.6 mm (+23% increase), and the predissection diameter showed a significant difference from the postdissection TL maximum diameter (30.5 versus 28.5 mm, P <0.0001).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Okuno et al15 reported an increase in the descending aorta from 10.9±2.9 to 12.9±3.8 mm after induced dissection in an experimental study using the swine model. Rylski et al11 reported a geometrical change in the descending aorta in 25 patients with acute type B aortic dissection compared with enhanced CT scans within 2 years before dissection, which is similar to the present study. They found that the mean total diameter changed from 28.2 to 34.6 mm (+23% increase), and the predissection diameter showed a significant difference from the postdissection TL maximum diameter (30.5 versus 28.5 mm, P <0.0001).…”
Section: Discussionsupporting
confidence: 90%
“…The cross‐sectional area and CL of the TL are affected by the shape of the decompressed TL. In Rylski et al's11 study, the severity of TL decompression was not addressed, and we thus could not compare our results with their results.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…However, compared with healthy elderly individuals in Asian populations, uncomplicated patients with IMHB showed clear changes in the diameters of the ascending aorta (39.4 ± 6.7 mm) and descending aorta (34.5 ± 7.9 mm) and the arch angle (103.8 ± 25 degrees) . Rylski et al reported similar geometric changes before and after the onset of acute aortic syndromes, including aortic dilatation and increased aortic tortuosity. Schäfer also demonstrated in patients with elevated aortic stiffness that the wall shear stress and time‐averaged wall shear stress were significantly reduced from zones 1 to 4 and the oscillatory shear index was significantly elevated in zones 0, 1, and 4, which predicted the development of severe aortopathy.…”
Section: Discussionmentioning
confidence: 92%